2004
DOI: 10.1590/s0041-87812004000400001
|View full text |Cite
|
Sign up to set email alerts
|

Causes of low vision and use of optical aids in the elderly

Abstract: PURPOSE:To determine the causes of low vision in an elderly population attended by a university visual rehabilitation service and to check for the use of prescribed optical aids.METHOD: A cross-sectional study was carried out on patients aged 60 years or over attending for the first time a university low vision service in 2001. Ophthalmic reevaluation and interview were performed by means of a structured questionnaire in 2002.RESULTS: The sample comprised 50 subjects aged between 60 and 90 years. Severe low vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0
7

Year Published

2006
2006
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 8 publications
1
17
0
7
Order By: Relevance
“…Of those 60.0%, the majority (88.8%) reported the use of spectacles and lenses to perform close manual activities (Table 1). Carvalho et al (16) reported similar findings in their study, where 60% subjects reported the use of optical aids. These patients achieved considerable improvement in visual acuity when they used prescriptions for near distance vision in accordance with their visual needs.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…Of those 60.0%, the majority (88.8%) reported the use of spectacles and lenses to perform close manual activities (Table 1). Carvalho et al (16) reported similar findings in their study, where 60% subjects reported the use of optical aids. These patients achieved considerable improvement in visual acuity when they used prescriptions for near distance vision in accordance with their visual needs.…”
Section: Discussionsupporting
confidence: 69%
“…It is important for the physician or the rehabilitation team to explain the purposes of the aids to enable the patient to make the best use of his or her residual vision (16) . Sacks (19) mentioned that the use of optical aids can increase the self-esteem of subjects with low vision.…”
Section: Discussionmentioning
confidence: 99%
“…(24) Study developed in 2004 (27) found that 54.8% of patients attending the Low Vision Service (LVS) at Universidade Estadual de Campinas were prescribed optical aids. Optical aids were not prescribed for those patients who no longer performed activities of reading and writing, those who considered their level of vision satisfactory to perform everyday activities, those who had high-grade myopia with visual acuity at close-up of 1 M or 0.8 M (being able to read words in newspapers/magazines) and those with very severe eye disease.…”
Section: Nutritionistmentioning
confidence: 99%
“…No que diz respeito à escolaridade 68,7% dos pacientes do grupo estudado, tinham o ensino médio e superior, e a utilização de ajudas óticas pode proporcionar benefícios pessoais e sociais, aumentando a autonomia e melhorando a qualidade de vida. 11 A população estudada não apresentou diferença significativa em relação ao sexo, conforme já descrito na literatura. 12 O glaucoma, causa prevalente de deficiência visual entre nossos usuários, pela alta freqüência de incapacidade que acarreta é considerada um problema de saúde pública 13 e situa-se entre as principais causas de cegueira em população idosa 10 .…”
Section: -Discussãounclassified